PRIORITAS PENANGANAN JALAN DENGAN SISTEM MANAJEMEN JALAN DI KABUPATEN LOMBOK UTARA - YUCYINTHA ANJANI; I DEWA MADE ALIT KARYAWAN; MADE MAHENDRA (GANEC SWARA, 2023)
Obstacles faced by the Government in carrying out road preservation activities are differences in perceptions of handling priorities from both the Regional Government and the community and budget constraints. The source of the data is the results of observations in the field and data on sub-district roads in Pemenang District, North Lombok Regency. The types of data used are primary data and secondary data to obtain the research objective, namely to analyze priority handling of roads that will be rehabilitated/repaired and/or maintained on a regular basis. Based on the results of data processing using PKRMS, it can be concluded that the priority for handling the road and the recommendations for handling it are the Linker Selatan Pemenang – Tanjung road section which is the first priority with recommendations for handling rehabilitation in the first year and periodically in the third and fifth years. In second place is the Pemenang-Tebango Bolot road section with recommendations for treatment, namely rehabilitation in the first year and periodically in the second year. Furthermore, the Mubasirun-Terengan road section with recommendations for handling rehabilitation in the first year. In fourth place is the Pemenang-Bangsal road section with recommendations for handling rehabilitation in the first year and periodic maintenance in the second and fifth years.